2019
DOI: 10.1002/chem.201902057
|View full text |Cite
|
Sign up to set email alerts
|

A Cucurbit[8]uril 2:2 Complex with a Negative pKa Shift

Abstract: A viologen derivative carrying a benzimidazole group (V-P-I 2+ ) can be dimerized in water using cucurbit [8]uril (CB[8]) in the form of a 2:2 complex resulting in a negative shift of the guest pKa, by more than 1 pH unit, contrasting with the positive pKa shift usually observed for CB-based complexes. While 2:2 complex protonation is unclear by NMR, silver cations have been used for probing the accessibility of the imidazole groups of the 2:2 complexes. The protonation capacity of the buried imidazole groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 103 publications
3
25
0
Order By: Relevance
“…found that, alinear and rigid imidazole derivative of methylviologen assembled as a2:2 complex with CB [8] (Figure 6), exhibiting an unusual, negative pK a shift. [56] This result is counter-intuitive as the very large majority of CB complexes show positive pK a shift, but could be ration- Figure 2. Main ditopic guest molecules affording oligomeric, or polymeric assemblies with CB [8].T he H-H (Head-to-Head) versus H-T (Head-to-Tail) arrangements are important,a sflexibility,rigidity,orangles between building-blocks.…”
Section: Minireviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…found that, alinear and rigid imidazole derivative of methylviologen assembled as a2:2 complex with CB [8] (Figure 6), exhibiting an unusual, negative pK a shift. [56] This result is counter-intuitive as the very large majority of CB complexes show positive pK a shift, but could be ration- Figure 2. Main ditopic guest molecules affording oligomeric, or polymeric assemblies with CB [8].T he H-H (Head-to-Head) versus H-T (Head-to-Tail) arrangements are important,a sflexibility,rigidity,orangles between building-blocks.…”
Section: Minireviewsmentioning
confidence: 99%
“…Finally,i ntroduction of relevant groups on the guest has imparted new properties for these assemblies.Azatype recognizing blocks in ditopic guests allowed modulating the stoichiometry of CB [8] complexes, [58,59,70] that have also showed new properties,specific of the n:n arrangements such as conformational control, [60] fluorescence control [51,53,55,71,73,75] or unusual pK a shift. [56] Finally,ahybrid covalent:non-covalent approach with af unctionalized CB [6] afforded daisy-chain dimers featuring two cavities and two guest fragments. [85] 2.3.…”
Section: General Trends About 2:2c Omplexesmentioning
confidence: 99%
“…a molecule with signicant rigidity. 28,29 For instance, various rigid molecular moieties such as benzidine, 30 benzothiazole, 31,32 arylpyridinium, 28,33 arylterpyridyl, 34 bipyridinium, 35 and benzimidazole 29 have been employed to produce CB[8]-mediated 2 : 2 complexes. Herein, we present a general and modular strategy towards the dimerization of arbitrary functional components (uorophores in this work) by connecting them to multiple rigid modules that can be "clamped" together by CB [8] complexation.…”
Section: Introductionmentioning
confidence: 99%
“…Negative p K a shift in 2:2 complexes. In parallel, Yin et al. found that, a linear and rigid imidazole derivative of methyl‐viologen assembled as a 2:2 complex with CB[8] (Figure 6), exhibiting an unusual, negative p K a shift [56] …”
Section: Discrete Cucurbituril N:n Complexesmentioning
confidence: 92%